Neural stem cells in adult neurogenesis and their therapeutic applications in neurodegenerative disorders: a concise review - Teketay Bayleyegn Derso; Bemrew Admassu Mengistu; Yitayew Demessie; Melkie Dagnaw Fenta; Kalkidan Getnet (Frontiers in Molecular Medicine)
The idea of ​​using stem cell therapy to treat neurodegenerative diseases has undergone significant change over the years and has made significant progress recently. Neurotrophins, growth factors, and transcription factors regulate neural stem cell proliferation and differentiation. Disruption of these regulatory mechanisms, including negative feedback, can contribute to neurodegenerative diseases. Contemporary research highlights a growing global concern regarding diverse neurodegenerative disorders affecting both humans and animals. These conditions arise from neuronal cell death, axonal regeneration failure, and impairment of neuronal structure. Current pharmacological treatments primarily offer symptomatic relief without altering disease progression. Consequently, researchers are investigating innovative therapeutic strategies, with neural stem cell therapy emerging as a promising avenue. Adult neural stem cells, embryonic neural stem cells, and induced pluripotent stem cells represent potential cell sources, although challenges such as ethical considerations and technical limitations remain. The therapeutic application of neural stem cells holds significant promise for addressing neurodegenerative diseases, including Alzheimer’s disease, stroke, amyotrophic lateral sclerosis, spinal cord injury, and multiple sclerosis. Neural stem cell therapy aims to replenish lost neurons and promote neural regeneration in these conditions. While clinical trials have demonstrated some success in improving cognitive and motor functions in individuals with neurodegenerative impairments, challenges such as immunological rejection, the identification of compatible cell sources, ethical concerns, treatment efficacy, and potential side effects necessitate thorough investigation before widespread clinical implementation. Despite these challenges, neural stem cell-based therapy offers substantial potential for revolutionizing the treatment of neurodegenerative diseases and central nervous system injuries. This paper, therefore, explores adult neurogenesis and the therapeutic potential of neural stem cells within the dynamic field of neurodegenerative disorders.